Gender, availability and dual emancipation in the Swedish ICT sector. (April 2017) - Holth, Line; Bergman, Ann; MacKenzie, Robert
Set in the context of the Swedish state's agenda of dual emancipation for women and men, the article shows how a global ICT consultancy company's formal gender equality goal is undermined by competing demands. Employing the concept of availability, in preference to work–life balance, the research found women opted out of roles requiring high degrees of spatial and temporal availability for work, in favour of roles more easily combined with family responsibilities. Such choices led to poor career development, plus the loss of technological expertise and confidence. These outcomes were at odds with the company's gender equality aims, as well as government objectives to make it easier for women and men to combine work and family, and increase the number of women within ICT.